The handmade alphabet - Rankin, Laura (New York : Dial Books, 1991)
Presents the handshape for each letter of the American manual alphabet accompanied by an object whose name begins with that letter.
Keywords: Finger spelling -- United States; Finger spelling; Sign language; Alphabet; Deaf